Peripheral Neurectomy With Customized Nerve Reconstruction for Periorbital Neuropathic Pain: Initial Experience and Clinical Outcomes. Issue 6 (20th May 2022) - Kim, Jane S.; Tian, James; Gross, Andrew; Aggarwal, Sahil; May, Lauren; Leyngold, Ilya M.
Abstract : Purpose: To describe a novel, minimally invasive surgical technique to treat severe, intractable periorbital neuropathic pain. Methods: A retrospective analysis of patients with severe, treatment-refractory periorbital pain who underwent transection of affected sensory trigeminal branches with nerve repair was performed. Collected data included etiology and duration of neuropathic pain, comorbidities, prior treatment history, surgical technique including site of transected sensory nerves and type of nerve repair, preoperative and postoperative pain scores as well as follow-up duration. Differences between preoperative and postoperative values were analyzed by the Wilcoxon signed-rank test. Results: A total of 5 patients with severe periorbital neuropathic pain underwent transection of affected supraorbital, supratrochlear, infratrochlear, infraorbital, zygomaticotemporal, and zygomaticofacial nerves with customized nerve reconstruction. All 5 had improvement of periorbital pain after surgery, with 3 (60%) noting complete resolution of pain and 2 (40%) experiencing partial pain relief over a median follow-up period of 9 months (interquartile range [IQR], 6–19 months). Of the 3 patients who had complete resolution of pain, all reported continued pain relief. Median McGill pain scores significantly decreased from 8.4 (IQR, 8.2–10.0) preoperatively to 0.0 (IQR, 0.0–4.8; p < 0.001) postoperatively. All patients reported satisfaction with the surgical procedure and stated that they would undergo the procedure again if given the option. One patient with history of postherpetic neuralgia (PHN) had reactivation of herpes zoster at postoperative month 3, which was self-limited, without worsening of her neuropathic pain. Another patient with PHN required a staged procedure to achieve complete pain relief. Conclusion: Peripheral neurectomy with customized reconstruction of involved sensory nerves can successfully reduce and even eradicate periorbital neuropathic pain that was previously recalcitrant to combination pharmacotherapy and prior neurolysis procedures. Abstract : Peripheral neurectomy with customized nerve reconstruction may reduce and even completely resolve periorbital neuropathic pain that was previously refractory to combination pharmacotherapy and neurolysis.